The Effect of Work Discipline and Work Competence on Employee Performance at PT Surya Rengo Containers - Mohamad Irfan; Cecep Haryoto (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study examines the contribution of work discipline and work competence to employee performance at PT Surya Rengo Containers. Employing a quantitative-associative design, data were collected through questionnaires distributed to 80 employees and analyzed using multiple linear regression with SPSS. The results indicate that work discipline has a positive and significant effect on employee performance (t = 6.389; p < 0.001). Similarly, work competence demonstrates a positive and significant influence (t = 6.585; p < 0.001). Simultaneously, both variables significantly affect employee performance (F = 77.023; p < 0.001). The coefficient of determination (R² = 0.667) shows that work discipline and work competence collectively explain 66.7% of the variance in employee performance, while the remaining 33.3% is attributed to other factors not included in this study. These findings suggest that enhancing employee performance requires strengthening adherence to organizational rules and punctuality, as well as continuous development of employees’ knowledge, technical skills, attitudes, and interpersonal competencies. The study highlights the strategic importance of discipline and competence as key determinants of organizational effectiveness.